Mobilités et immobilités des populations insulaires bretonnes : quand le quotidien influence les choix résidentiels - Frédéric Audard; Pauline Jézéquel; Laurence David (Espace populations sociétés)
Islands, marked by remoteness and low economic diversity, have a unique demographic dynamic. Their relationship with the mainland is evolving, and recent demographic changes are deeply altering their territorial connections, exacerbating their geographical and social marginality.This article aims to study the relationship between daily mobility and residential mobility in this complex insular context. Our analysis first focuses on the residential mobility of populations toward metropolitan French island contexts, then on the specificities of daily mobility for islanders, and finally on the links that underlie the relationship between daily and residential mobility.These analyses reveal a dual logic of constraint: daily mobility, heavily conditioned by the geographical situation of islands, leads certain population categories to relocate towards metropolitan areas and large ports. Thus, for reasons related to employment, education, and changes in family structure, migrations toward the mainland are observed, sometimes making the return journey difficult.